A Oração do Senhor: um estudo exegético de Lc 11,2d-4 - Silva, Renata Soares da (2025)
This dissertation focuses on the Lucan version of the Lord’s Prayer (Luke 11:2d-4), commonly known as the Our Father. This prayer is considered the prayer par excellence of Christianity, carrying profound meanings that permeate communal and liturgical contexts. However, it should be noted that the Lucan version, with its five petitions, is less commonly used among Christians than the Matthean version. This research is justified by the significance of the Lord's Prayer in biblical theology and in Jewish-Christian dialogue, as it finds parallels in the Jewish liturgical tradition from the late Second Temple period. The main objective was to conduct an exegetical study of Luke 11:2d-4. For this purpose, the research investigated: its immediate and broader co-texts, the daily Jewish prayers from the late Second Temple period, textual variants, linguistic-syntactic, semantic, and textual cohesion analyses, and engaged in theological reflection through a pragmatic approach. Using a methodology centered on a synchronic approach and a pragma-linguistic perspective, the interaction between the biblical text and its readers was highlighted, both in its original context and in contemporary applications. The results indicate that the Lord’s Prayer, taught by Jesus as a "model of prayer" rooted in the values of the Kingdom of God, shaped and still shapes the identity of his followers, fostering another way of living. Furthermore, the study revealed connections between Jewish and Christian traditions, emphasizing the prayer’s significance as an element that promotes faith, justice, and hope. Thus, the research contributes to a deeper theological understanding and the strengthening of interreligious dialogue, aligning with the Conciliar Fathers' desire to foster mutual knowledge and collaboration between Christians and Jews